A composite positive electrode material and its preparation method and application
By using wet method to prepare the lithium ferrate coating in the positive electrode material of lithium-ion batteries, the problems of manganese dissolution and poor conductivity are solved, and the circulation performance and energy density of the battery are improved.
Patent Information
- Application Number
- CN202211609861.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-14
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2042-12-14
AI Technical Summary
The existing lithium-ion battery positive electrode materials have problems with manganese dissolution, poor conductivity, and the negative electrode materials consume active Li+ during the first charge, resulting in low battery energy density and capacity.
The wet method is used to first form the Fe(OH)3 precursor, and then sintered to prepare the lithium ferrate material to form a uniform lithium ferrate coating to prevent the core material from contacting the electrolyte and improve the conductivity and cycling performance.
Effectively improve manganese dissolution, improve material conductivity and rate performance, and ensure battery capacity and energy density.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of lithium ion batteries and relates to a composite positive electrode material and a preparation method and application thereof. Background Art
[0002] In order to cope with more usage scenarios, lithium-ion batteries need higher energy density, and the specific capacity and voltage of the positive electrode material will directly affect the specific energy of the battery. Among them, the phosphate-based positive electrode material LiFe with olivine structure 1- X Mn X PO4 has the advantages of both lithium iron phosphate and lithium manganese phosphate. Its operating voltage is 3.5-4.1V. The presence of Fe can reduce the dissolution of Mn, thereby improving the cyclic performance of the material.
[0003] LiFe 1-x Mn x Although the Fe element in the PO4 positive electrode material can reduce the dissolution of Mn, the positive electrode material still has the problem of manganese dissolution due to direct contact with the electrolyte, and the conductivity of the material is still poor, which needs to be further improved. At the same time, during the first charging process of the lithium-ion battery, the negative electrode material will permanently consume more active Li from the positive electrode. + , a SEI film is formed on the surface of the negative electrode, which reduces the capacity and energy density of the lithium-ion battery.
[0004] CN115207332A discloses a lithium iron manganese phosphate composite material and a preparation method thereof, a positive electrode material, and a lithium battery. The lithium iron manganese phosphate composite material includes lithium iron manganese phosphate particles and a coating layer wrapped around the surface of the lithium iron manganese phosphate particles, wherein the coating layer contains carbon and lithium iron borate.
[0005] CN107128892A discloses a method for preparing a lithium iron manganese phosphate positive electrode material. The method uses an iron source, a phosphorus source, a manganese source, a lithium source, and a carbon source to sinter to prepare the lithium iron manganese phosphate positive electrode material. The phosphorus source, the iron source, the manganese source, and the lithium source are put into a reactor, and pure water is added at a solid content of 5 to 60% and stirred and mixed; a carbon source is added at a solid content mass ratio of 50 to 200%; the mixture is stirred and mixed at a temperature of 120 to 150° C. in the reactor; the material is spray-dried; the material is calcined in a nitrogen atmosphere; and the material is tunnel-dried.
[0006] After the lithium iron manganese phosphate positive electrode material in the above scheme is made into a battery, the negative electrode material in the battery will permanently consume the active Li from the positive electrode. + , a SEI film is formed on the surface of the negative electrode, resulting in low energy density and capacity of the battery. Summary of the invention
[0007] The object of the present invention is to provide a composite positive electrode material and a preparation method and application thereof. The composite positive electrode material prepared by the method of the present invention has high thermal stability, can effectively improve manganese dissolution, increase material conductivity, and improve material rate performance and cycle performance.
[0008] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:
[0009] In a first aspect, the present invention provides a method for preparing a composite positive electrode material, the preparation method comprising the following steps:
[0010] (1) mixing the core material with a solvent to obtain a suspension, stirring the suspension and adding an iron source and a precipitant to react;
[0011] (2) The material obtained by the reaction in step (1) is mixed with a lithium source, and the mixture is sintered to obtain the composite positive electrode material.
[0012] The present invention adopts a wet method to first form a Fe(OH)3 precursor, and then sinter to prepare a lithium ferrite material, so that the lithium ferrite can be evenly coated on the surface of the core material. The lithium ferrite material formed after the first charge will also be evenly coated on the surface of the core material. The coating of the lithium ferrite material prevents the core layer material from directly contacting the electrolyte, further reduces the dissolution of Mn, and is beneficial to improving the cycle performance of the material. At the same time, lithium ferrite is a fast ion conductor material, which increases the Li + The transmission channel improves the ionic conductivity of the material and improves the material's rate performance.
[0013] Preferably, the chemical formula of the core material in step (1) is LiFe 1-x-a Mn x M a PO4, wherein M comprises any one of Ti, Zr or Al or a combination of at least two thereof, 0.5≤x≤0.9, 0.01≤a≤0.05.
[0014] Preferably, the solvent comprises deionized water.
[0015] Preferably, the mass concentration of the suspension is 1.2-1.5 g / cm 3 , for example: 1.2g / cm 3 , 1.25g / cm 3 , 1.3g / cm 3 , 1.4g / cm 3 or 1.5g / cm 3 wait.
[0016] Preferably, the iron source in step (1) includes any one of ferric sulfate, ferric chloride or ferric nitrate, or a combination of at least two of them.
[0017] Preferably, the mass ratio of the iron source to the core material is (0.03-0.15):1, for example: 0.03:1, 0.05:1, 0.08:1, 0.1:1 or 0.15:1, etc.
[0018] Preferably, the precipitant comprises at least one of a sodium hydroxide solution and a potassium hydroxide solution.
[0019] Preferably, the pH of the precipitant is 9 to 13, for example, 9, 10, 11, 12 or 13, etc.
[0020] Preferably, the mass ratio of the precipitant to the core material is (0.04-0.11):1, for example: 0.04:1, 0.05:1, 0.08:1, 0.1:1 or 0.11:1, etc.
[0021] Preferably, the reaction temperature in step (1) is 20-70°C, for example, 20°C, 30°C, 40°C, 60°C or 70°C.
[0022] Preferably, the reaction time is 8 to 15 hours, for example, 8 hours, 9 hours, 10 hours, 12 hours or 15 hours.
[0023] Preferably, after the reaction, the obtained product is filtered, washed and rinsed with water.
[0024] Preferably, the lithium source in step (2) includes any one of lithium hydroxide, lithium oxide or lithium carbonate, or a combination of at least two of them.
[0025] Preferably, the mass ratio of the lithium source to the material is (0.03-0.14):1, for example: 0.03, 0.05, 0.08, 0.1 or 0.14, etc.
[0026] Preferably, the atmosphere of the sintering treatment in step (2) includes any one of nitrogen, helium or argon, or a combination of at least two of them.
[0027] Preferably, the sintering temperature is 600-1000°C, for example, 600°C, 700°C, 800°C, 900°C or 1000°C.
[0028] Preferably, the sintering treatment time is 8 to 15 hours, for example: 8 hours, 9 hours, 10 hours, 12 hours or 15 hours.
[0029] In a second aspect, the present invention provides a composite positive electrode material, which is prepared by the method described in the first aspect, and comprises a core and a lithium ferrite coating layer disposed on the surface of the core.
[0030] The positive electrode material of the present invention has a core LiFe1-x-a Mn x M a The presence of manganese in PO4 material can improve the energy density of the material. At the same time, the matrix material is doped with other elements, which creates defects inside the crystal. These defects are beneficial to Li + The diffusion of the material is improved, and due to the different charge states, a charge difference is generated, and a cation vacancy is formed through a charge compensation mechanism, which improves the conductivity of the material, thereby improving the rate performance of the material. The coating layer of lithium ferrite material is used as a lithium supplement, which can make up for the active lithium consumed in the formation of the SEI film during the first charge and the repair of the SEI film during the cycle, which ensures the capacity and energy density of the positive electrode material.
[0031] Preferably, based on the mass of the composite positive electrode material being 100%, the mass fraction of the inner core is 90-95%, for example, 90%, 91%, 92%, 93%, 94% or 95%.
[0032] Preferably, the mass fraction of the lithium ferrite coating layer is 5-10%, for example, 5%, 6%, 7%, 8%, 9% or 10%.
[0033] In a third aspect, the present invention provides a positive electrode plate, wherein the positive electrode plate comprises the composite positive electrode material as described in the second aspect.
[0034] In a fourth aspect, the present invention provides a lithium-ion battery, wherein the lithium-ion battery comprises the positive electrode sheet as described in the third aspect.
[0035] Compared with the prior art, the present invention has the following beneficial effects:
[0036] (1) The composite positive electrode material prepared by the method of the present invention has high thermal stability, can effectively improve manganese dissolution, increase material conductivity, and improve material rate performance and cycle performance.
[0037] (2) In the positive electrode material prepared by the present invention, the presence of manganese in the core material can improve the energy density of the material. At the same time, the base material is doped with other elements, and the doping causes defects in the crystal. These defects are conducive to Li +Diffusion, and due to the different charge valence states, a charge difference is generated, and cation vacancies are formed through the charge compensation mechanism, which improves the conductivity of the material, thereby improving the rate performance of the material. The coating layer Li5FeO4 material, as a lithium supplement, can make up for the active lithium consumed in the formation of the SEI film during the first charge and the repair of the SEI film during the cycle, which effectively guarantees the capacity and cycle performance of the positive electrode material. At the same time, the Fe(OH)3 precursor is first prepared by a wet process, and then sintered to form the Li5FeO4 material, so that Li5FeO4 can be evenly coated on the surface of the core material. The LiFeO2 material formed after the first charge will also be evenly coated on the surface of the core material, effectively playing the coating role of the LiFeO2 material, preventing the core layer material from directly contacting the electrolyte, further reducing the dissolution of Mn, and is beneficial to improving the cycle performance of the material. At the same time, LiFeO2 is a fast ion conductor material, which increases the Li on the surface of the positive electrode material. + The transmission channel improves the ionic conductivity of the material and improves the material's rate performance. DETAILED DESCRIPTION
[0038] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0039] The parts in the examples and comparative examples of the present invention are parts by mass unless otherwise specified.
[0040] The preparation method of the core material is as follows:
[0041] According to the molar ratio of Fe:Mn:M=0.38:0.6:0.02, iron sulfate, manganese sulfate, titanium tetrachloride, and lithium source are uniformly mixed in deionized water, and a solution prepared by phosphoric acid is added while stirring, and the reaction is carried out at 30°C for 5 hours, and then the product is filtered and washed until the pH of the washing water is neutral, and the precipitate is placed at 90°C for vacuum drying for 25 hours, and then the dried precipitate is transferred to an atmosphere furnace, and sintered at 250°C for 4 hours and then sintered at 600-800°C for 12 hours under an inert atmosphere to obtain LiFe 0.38 Mn 0.6 Ti 0.02 PO4 core material.
[0042] Example 1
[0043] This embodiment provides a composite positive electrode material, and the preparation method of the composite positive electrode material is as follows:
[0044] (1) 1 part of the core material is placed in deionized water and stirred to form a uniform suspension with a mass concentration of 1.3 g / cm, and then 0.12 parts of ferric sulfate and 0.10 parts of a sodium hydroxide solution with a pH of 11 are slowly added while stirring, and the mixture is reacted at 50° C. for 6 h, and then the product is filtered and washed until the pH of the washing water is neutral, and the precipitate is placed at 90° C. and vacuum dried for 25 h to obtain a coated intermediate material;
[0045] (2) One part of the coated intermediate material is uniformly mixed with 0.12 parts of lithium carbonate, and then transferred to an atmosphere furnace and sintered at 800° C. for 12 hours under nitrogen to obtain the composite positive electrode material, in which the mass fraction of the core in the composite positive electrode material is 92%, and the mass fraction of the Li5FeO4 coating layer is 8%.
[0046] Example 2
[0047] This embodiment provides a composite positive electrode material, and the preparation method of the composite positive electrode material is as follows:
[0048] (1) 1 part of the core material is placed in deionized water and stirred to form a uniform suspension with a mass concentration of 1.4 g / cm, and then 0.11 parts of ferric sulfate and 0.09 parts of a potassium hydroxide solution with a pH of 10 are slowly added while stirring, and the mixture is reacted at 55° C. for 5 h, and then the product is filtered and washed until the pH of the washing water is neutral, and the precipitate is placed at 92° C. and vacuum dried for 25 h to obtain a coated intermediate material;
[0049] (2) One part of the coated intermediate material was uniformly mixed with 0.11 parts of lithium carbonate, and then transferred to an atmosphere furnace and sintered at 750° C. for 12 hours under nitrogen to obtain the composite positive electrode material, in which the mass fraction of the core in the composite positive electrode material was 93%, and the mass fraction of the Li5FeO4 coating layer was 7%.
[0050] Example 3
[0051] The only difference between this embodiment and embodiment 1 is that the mass ratio of the iron source to the core material is 0.02:1, and the other conditions and parameters are exactly the same as those in embodiment 1.
[0052] Example 4
[0053] The only difference between this embodiment and embodiment 1 is that the mass ratio of the iron source to the core material is 0.2:1, and the other conditions and parameters are exactly the same as those in embodiment 1.
[0054] Example 5
[0055] The only difference between this embodiment and embodiment 1 is that the mass ratio of the coated intermediate material (material) to the lithium source is 1:0.02, and the other conditions and parameters are exactly the same as those in embodiment 1.
[0056] Example 6
[0057] The only difference between this embodiment and embodiment 1 is that the mass ratio of the coated intermediate material (material) to the lithium source is 1:0.2, and the other conditions and parameters are exactly the same as those in embodiment 1.
[0058] Comparative Example 1
[0059] The only difference between this comparative example and Example 1 is that the core material and the Li5FeO4 material are directly ground and coated.
[0060] Performance Test:
[0061] The positive electrode materials synthesized in Examples 1 to 6 and Comparative Example 1 are used to prepare lithium-ion batteries, and the preparation method is as follows:
[0062] Preparation of positive electrode sheet: After fully stirring the above positive electrode material, conductive carbon black and polyvinylidene fluoride in a mass ratio of 90:5:5, N-methylpyrrolidone is added to obtain positive electrode slurry, the prepared slurry is coated on aluminum foil, cold pressed, baked and die-cut into strips to prepare positive electrode sheets;
[0063] Preparation of negative electrode sheet: After fully mixing the negative electrode active material graphite, conductive carbon black and sodium carboxymethyl cellulose in a mass ratio of 92:4:4, deionized water is added to obtain negative electrode slurry, the prepared slurry is coated on copper foil, cold pressed, baked and die-cut into strips to prepare negative electrode sheets;
[0064] Preparation of electrolyte: 1 mol LiPF6 was used as the lithium salt, and the solvent was a mixed solvent consisting of EC / DC / EMC (volume ratio of 1:1:1).
[0065] Preparation of lithium-ion batteries: The positive electrode sheet, polypropylene separator and negative electrode sheet are wound into a core with a certain pressure, and the prepared core is placed in an aluminum shell. Under negative pressure conditions, the electrolyte is injected into the battery cell. After sufficient rest, subsequent processes such as packaging, formation and capacity division are carried out to obtain a lithium-ion battery.
[0066] The test method is as follows:
[0067] Rate performance: The lithium secondary battery was charged at 1C under constant current conditions at 25°C until 4.2V / 0.05C, and then discharged at 3C under constant current (CC) conditions to 2.8V, and the discharge specific capacity was calculated;
[0068] Cycle performance: The lithium secondary battery was charged at 1C under constant current conditions at 25°C until 4.2V / 0.05C, and then discharged at 1C under constant current (CC) conditions to 2.8V. This was considered as one cycle, and the test was repeated for 1000 cycles. The capacity retention rate of the 1000th cycle during the charge and discharge process was measured.
[0069] The test results are shown in Table 1:
[0070] Table 1
[0071] First discharge specific capacity at 3C rate Capacity retention after 1000 cycles at 1C rate Example 1 151mAh / g 98.2% Example 2 152mAh / g 98.0% Example 3 149mAh / g 96.5% Example 4 144mAh / g 97.9% Example 5 144mAh / g 96.3% Example 6 148mAh / g 96.2% Comparative Example 1 140mAh / g 94.5%
[0072] As can be seen from Table 1, from Examples 1-2, the first discharge specific capacity of the battery made of the composite positive electrode material of the present invention at a rate of 3C can reach more than 151 mAh / g, and the capacity retention rate can reach more than 98% after 1000 cycles at a rate of 1C.
[0073] By comparing Example 1 with Examples 3-4, it can be seen that in the preparation process of the composite positive electrode material of the present invention, the mass ratio of the iron source and the core material will affect the performance of the composite positive electrode material. The mass ratio of the iron source and the core material is controlled at 0.03-0.15:1, and the performance of the composite positive electrode material is better. If the mass ratio of the iron source and the core material is too low, the mass fraction of the coating material is small, the LiFeO2 formed after the first discharge cannot form a complete coating layer, the coating effect cannot be fully exerted, and the improvement of the material cycle performance is limited; if the ratio of the iron source and the core material is too high, the mass fraction of the coating material is large, and since the LiFeO2 material does not provide discharge capacity, if there is too much LiFeO2 material, the capacity and energy density of the positive electrode material will be reduced.
[0074] By comparing Example 1 with Examples 5-6, it can be seen that in the preparation process of the composite positive electrode material of the present invention, the mass ratio of the lithium source and the material will affect the performance of the composite positive electrode material. When the mass ratio of the lithium source and the material is controlled at 0.03-0.14:1, the performance of the composite positive electrode material is better. If the mass ratio of the lithium source and the material is too low, the lithium content of the formed coating layer material is low, and the lithium replenishing agent cannot play the role of replenishing lithium during the first discharge and cycle process, thereby reducing the capacity and cycle performance of the positive electrode material; if the mass ratio of the lithium source and the material is too high, the excessive lithium content not only increases the production cost, but also causes a high residual alkali on the surface of the material, affecting the cycle stability of the material and reducing the cycle stability.
[0075] By comparing Example 1 with Comparative Example 1, it can be seen that the present invention adopts a wet method to first form a Fe(OH)3 precursor, and then sinter to prepare a lithium ferrite material, so that the lithium ferrite can be evenly coated on the surface of the core material. The LiFeO2 material formed after the first charge will also be evenly coated on the surface of the core material. The coating of the LiFeO2 material prevents the core layer material from directly contacting the electrolyte, further reducing the dissolution of Mn, which is beneficial to improving the cycle performance of the material. At the same time, LiFeO2 is a fast ion conductor material, which increases the Li + The transmission channel improves the ionic conductivity of the material and improves the material's rate performance.
[0076] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.
Claims
1. A method for preparing a composite positive electrode material, characterized in that: The preparation method comprises the following steps: (1) mixing the core material with a solvent to obtain a suspension, stirring the suspension and adding an iron source and a precipitant to react; The chemical formula of the core material is LiFe 1-x-a Mn x M a PO4, wherein M comprises any one or a combination of at least two of Ti, Zr or Al, 0.5≤x≤0.9, 0.01≤a≤0.05; (2) mixing the material obtained by the reaction in step (1) with a lithium source, and sintering the mixture to obtain the composite positive electrode material; The mass ratio of the lithium source to the material is (0.03-0.14):
1.
2. The preparation method according to claim 1, characterized in that The solvent includes deionized water.
3. The preparation method according to claim 1, characterized in that: The mass concentration of the suspension is 1.2-1.5 g / cm 3 .
4. The preparation method according to claim 1, characterized in that: The iron source in step (1) includes any one of ferric sulfate, ferric chloride or ferric nitrate, or a combination of at least two of them.
5. The preparation method according to claim 1, characterized in that: The mass ratio of the iron source and the core material in step (1) is (0.03-0.15):
1.
6. The preparation method according to claim 1, characterized in that: The precipitant in step (1) comprises sodium hydroxide solution and / or potassium hydroxide solution.
7. The preparation method according to claim 1, characterized in that: The pH of the precipitant in step (1) is 9-13.
8. The preparation method according to claim 1, characterized in that: The mass ratio of the precipitant to the core material in step (1) is (0.04-0.11):
1.
9. The preparation method according to claim 1, characterized in that: The reaction temperature in step (1) is 20-70°C.
10. The preparation method according to claim 1, characterized in that: The reaction time of step (1) is 8 to 15 hours.
11. The preparation method according to claim 1, characterized in that: After the reaction in step (1), the obtained product is filtered, washed and rinsed with water.
12. The preparation method according to claim 1, characterized in that: The lithium source in step (2) includes any one of lithium hydroxide, lithium oxide or lithium carbonate, or a combination of at least two of them.
13. The preparation method according to claim 1, characterized in that: The sintering atmosphere in step (2) includes any one of nitrogen, helium or argon, or a combination of at least two of them.
14. The preparation method according to claim 1, characterized in that: The sintering temperature in step (2) is 600-1000°C.
15. The preparation method according to claim 1, characterized in that: The sintering time in step (2) is 8 to 15 hours.
16. A composite positive electrode material, characterized in that: The composite positive electrode material is prepared by the method according to any one of claims 1 to 15, and the composite positive electrode material comprises a core and a lithium ferrite coating layer arranged on the surface of the core.
17. The composite positive electrode material according to claim 16, characterized in that: Taking the mass of the composite positive electrode material as 100%, the mass fraction of the inner core is 90-95%.
18. The composite positive electrode material according to claim 16, characterized in that: The mass fraction of the lithium ferrite coating layer is 5-10%.
19. A positive electrode plate, characterized in that: The positive electrode sheet comprises the composite positive electrode material as described in any one of claims 16 to 18.
20. A lithium ion battery, characterized in that: The lithium-ion battery comprises the positive electrode sheet as claimed in claim 19.
Citation Information
Patent Citations
Preparation method for lithium iron manganese phosphate positive electrode material
CN107128892A
Lithium manganese iron phosphate composite material and preparation method thereof, positive electrode material and lithium battery
CN115207332A
Lithium manganese iron phosphate positive electrode material as well as preparation method and application thereof
CN115020685A
Positive electrode active material and preparation method thereof, positive electrode and lithium secondary battery
CN115132977A